Second generation biol produced by homolactic fermentation of first generation biol - Flores Calderón, Elvis H. (2023)
The elaboration of Biol II-G was proposed to improve the properties of Biol I-G from cows, coming from a 10 m3 tubular biodigester which registered average values ​​of 7.05 pH and electrical conductivity 5.01 dS/m. For the preparation, lactic fermentation was carried out for a period of 5 days. The parameters that were evaluated in the biol samples were pH, lactic acidity, macronutrients (N, P, K), micronutrients, heavy and microbiological metals. The low pH in the fermentation ensured the elimination of pathogenic microorganisms. The results of the phytotoxicity test determined that the biol diluted to 0.1% contributed to the growth of lettuce.